MENINGKATKAN PEMAHAMAN KONSEP KEKONGRUENAN DAN KESEBANGUNAN PESERTA DIDIK MELALUI PEMBELAJARAN KOOPERATIF STAD - PRAMUDJI ENI (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
This study aims to improve the understanding of the mathematical concept of congruence and similarity in class IXB students of SMP Negeri 1 Piyungan semester 2 for the 2021/2022 academic year through the application of the Student Teams Achievement Division (STAD) Cooperative Model. This research is a classroom action research that uses the Kemmis & Taggart design in Jalaludin (2021:11) in class IXB of SMP Negeri 1 Piyungan, Bantul in the second semester of the 2021/2022 academic year. The type of action taken is Student Teams Achievement Division (STAD) Cooperative Learning. Data collection techniques used are observation and test learning outcomes. Observation techniques were used to record data about the interaction of students in groups, and learning outcomes tests were used to measure the level of success in understanding students' concepts of the subject matter. This research was carried out in two cycles, with the implementation technique, in groups the students discussed completing the LKPD activity I, then individually working on the LKPD activity II (quiz). Data from the understanding of students' concepts were analyzed using quantitative descriptive techniques. The results showed that from the average value of 64.50 with completeness of 23.33% in the initial conditions, after the first cycle of action the average value increased to 75.37 with completeness of 60%, and in the second cycle the average value increased to 75.37. the average score increased to 87.83 with a completeness of 90%. The conclusion of the researcher is that the understanding of the mathematical concept of congruence and congruence material of class IXB SMP Negeri 1 Piyungan, Bantul Regency increased after the implementation of Cooperative Learning Type Student Teams Achievement Division (STAD) in learning. ABSTRAKPenelitian ini bertujuan untuk meningkatkan Pemahaman Konsep matematika Materi Kekongruenan dan Kesebangunan pada Peserta Didik kelas IXB SMP Negeri 1 Piyungan semester 2 Tahun Pelajaran 2021/2022 melalui Penerapan Model Kooperatif Tipe Student Teams Achievement Division (STAD). Penelitian ini adalah penelitian tindakan kelas yang menggunakan desain Kemmis & Taggart dalam Jalaludin (2021:11) di kelas IXB SMP Negeri 1 Piyungan, Bantul pada semester dua Tahun Pelajaran 2021/2022. Jenis tindakan yang dilakukan adalah pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD). Teknik pengumpulan data yang digunakan adalah observasi dan tes hasil belajar. Teknik observasi digunakan untuk merekam data tentang interaksi Peserta Didik dalam kelompok, dan tes hasil belajar digunakan untuk mengukur tingkat keberhasilan pemahaman konsep peserta didik terhadap materi pelajaran. Penelitian ini terlaksana dalam dua siklus, dengan teknik pelaksanaan, secara berkelompok peserta didk berdiskusi menyelesaikan LKPD kegiatan I, kemudian secara individu mengerjakan LKPD kegiatan II (kuis). Data hasil pemahaman konsep peserta didik dianalisis dengan menggunakan teknik deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa dari rata-rata nilai yakni sebesar 64,50 dengan ketuntasan sebesar 23,33% pada kondisi awal, setelah dilakukan tindakan siklus I rata-rata nilai meningkat menjadi 75,37 dengan ketuntasan sebesar 60%, dan pada siklus II rata-rata nilai meningkat menjadi 87,83 dengan ketuntasan sebesar 90%. Simpulan peneliti adalah hasil pemahaman konsep Matematika materi kekongruenan dan kesebanguna peserta didik kelas IXB SMP Negeri 1 Piyungan Kabupaten Bantul meningkat setelah diterapkannya pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) dalam pembelajaran.